Konsep Pemeliharaan Anak Yatim Perspektif Al-Qur’an - Acep Ariyadri (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2021)
This paper discusses the concept of caring for orphans from the perspective of the Qur'an and relates it to the theory of maintaining an institution/foundation which has been recognized by the government. This study uses the method of thematic or maudhu'I exegesis, with the use of this method is expected to be an answer to the Qur'an to various problems that arise and can answer the problems of the Ummah. As the main conclusion of the study, all responsible parties; both government and society should be: firstly, both play a role in spreading a comprehensive understanding of the concept of good care of orphans, which refers to the Al-Qur'an and As-Sunnah. Secondly: there must be financial transparency in the management of funds, compensation, assets for orphans from the relevant foundations and institutions. Thirdly: all demands for financing education and health of orphan life are made free and all are borne by the government.